Drechslera dematioidea (Bubbák & Wróblewski) Subram. & Jain, A new fungal record for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2018)
Not available.Bangladesh J. Plant Taxon. 25(1): 119-121, 2018 (June)